PERAN STRATEGIS DAN KOMPETENSI PUBLIC RELATIONS RUMAH SAKIT INDONESIA DI ERA DISRUPTIF - Mahdalena Lubis (WACANA: Jurnal Ilmiah Ilmu Komunikasi, 2020)
Currently the hospital is being faced by the National Health Insurance disruptor which demands all hospitals to be aware of the emergence of competition and digitalization innovation in providing services and gaining public interest. Hospitals are required to adapt quickly to changes that occur in real time, but some of the roles and competencies of hospital public relations are not yet capable in carrying out their duties. This study aims to describe the role and competence of hospital public relations participants who took the competency test as many as 87 people during 2017-2019 from various regions in Indonesia. This qualitative case study descriptive study uses a mix of methods, surveys collect hospital's public relations personal data and in-depth interviews with representative subjects to get a complete picture. Data were analyzed using interactive techniques and triangulation techniques to validate data so that the data obtained would be more accurate. Strategic role refers to positions in structural and competence refers to the results of competency tests. The results of this study stated that most hospital public relations have a weak role and competence in dealing with the disruptive era. Education, experience and continuous training have a close relationship to become competent public relations. Efforts and solutions made in overcoming the existing reality are outlined in conclusions and suggestions.